2017
DOI: 10.14260/jemds/2017/150
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Number and Morphology of Cusps of Aortic Valve- Anatomical and Surgical Relevance

Abstract: BACKGROUNDThe human aortic valve is a vital structure and knowledge about its normal anatomy is important in detecting valve diseases and in valve replacement surgeries. The normal aortic valve has three semilunar leaflets or cusps, supported within the three aortic sinuses of Valsalva. The valve is known to exhibit anatomical variations with respect to number, shape and size of cusps, circumference and presence of fenestrations. The aim of the study is to detect and document the variations with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our present report is a unique combination of morphometrical assessments of the large population of autopsied human hearts as well as functional in vitro analyses of reanimated human hearts both studied to investigate aortic valve leaflets fenestrations. To date, during the last century, only four significant anatomical studies have investigated and reported on aortic valve fenestrations (Ashalatha & Hannah Noone, 2017; Foxe, 1929; Friedman & Hathaway, 1958; Losenno et al, 2012). A recent meta‐analysis of these studies showed the estimated prevalence of aortic valve fenestrations to be a high 55.9% in the general population (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present report is a unique combination of morphometrical assessments of the large population of autopsied human hearts as well as functional in vitro analyses of reanimated human hearts both studied to investigate aortic valve leaflets fenestrations. To date, during the last century, only four significant anatomical studies have investigated and reported on aortic valve fenestrations (Ashalatha & Hannah Noone, 2017; Foxe, 1929; Friedman & Hathaway, 1958; Losenno et al, 2012). A recent meta‐analysis of these studies showed the estimated prevalence of aortic valve fenestrations to be a high 55.9% in the general population (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic valve fenestrations, defined as an aperture/loss of tissue in the human aortic valve leaflets are common, but often overlooked entities, with unclear significances (Ashalatha & Hannah Noone, 2017; Friedman & Hathaway, 1958; Roberts et al, 2019; Whiteman et al, 2020; Zhu et al, 2020). It is estimated that they may be present in every second human, and in all age groups (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%